Chemoradiation Increases PD-L1 Expression in Certain Melanoma and Glioblastoma Cells - Derer, Anja; Spiljar, Martina; Bäumler, Monika; Hecht, Markus; Fietkau, Rainer; Frey, Benjamin; Gaipl, Udo S. (Frontiers in Immunology, 2016)
Immunotherapy approaches currently make their way into the clinics to improve the outcome of standard radiochemotherapy. The programmed cell death receptor ligand 1 (PD-L1) is one possible target that, upon blockade, allows T cell-dependent anti-tumor immune responses to be executed. To date it is unclear which radiochemotherapy protocol and which fractionation scheme leads to increased PD-L1 expression and thereby renders blockade of this immune suppressive pathway reasonable. We therefore investigated the impact of radiotherapy, chemotherapy and radiochemotherapy on PD-L1 surface expression on tumor cells of tumor entities with differing somatic mutation prevalence. Murine melanoma- (B16-F10), glioblastoma- (GL261-luc2), and colorectal- (CT26) tumor cells were treated with dacarbazine, temozolomide, and a combination of irinotecan, oxaliplatin and fluorouracil, respectively. Additionally they were irradiated with a single dose (10Gy) or hypo-fractionated (2x5Gy) respectively norm-fractionated (5x2Gy) radiation protocols were used. PD-L1 surface and intracellular IFN-gamma expression was measured by flow cytometry and IL-6 release was determined by ELISA. Further, tumor cell death was monitored by AnnexinV-FITC/7-AAD staining. For first in vivo analyses, the B16-F10 mouse melanoma model was chosen. In B16-F10 and GL261-luc2 cells, particularly norm-fractionated and hypo-fractionated radiation led to a significant increase of surface PD-L1, which could not be observed in CT26 cells. Further, PD-L1 expression is more pronounced on vital tumor cells and goes along with increased levels of IFN-gamma in the tumor cells. In melanoma cells chemotherapy was the main trigger for IL-6 release, while in glioblastoma cells it was norm-fractionated radiotherapy. In vivo, fractionated radiotherapy only in combination with dacarbazine induced PD-L1 expression on melanoma cells. Our results suggest a tumor-cell mediated up-regulation of PD-L1 expression following in particular chemoradiation that is not only dependent on the somatic mutation prevalence of the tumor entity.